A capacity margin for IP networks with QoS constraints and uncertain demands - Sharafeddine, Sanaa (2004)
IP network planning based on a given traffic demand becomes obsolete as soon as the actual traffic slightly deviates from the given values. It is highly probable that this be the case in IP networks with no deployed resource control mechanisms. Complex and comprehensive resource control mechanisms are still a matter of research; while the most practical and common scenario is to have control units at the ingress of the IP network as pertained by the differentiated services architecture (DiffServ). Based on this practical model, we study the distribution of traffic demand inside the network and introduce the concept of a capacity margin, which is added to the network links in order to account for a certain level of traffic demand variability. Moreover, we analytically calculate the capacity margin and investigate the tradeoff provided between the degree of network robustness and the consequent additional costs in terms of network resources. Finally, we show how such statistical consideration of traffic variability can offer high degrees of network robustness with rather low costs.